2021
DOI: 10.47197/retos.v44i0.90127
|View full text |Cite
|
Sign up to set email alerts
|

Exergame en educación: mapeando la investigación

Abstract: Este trabajo analiza los efectos del uso de exergames en la escuela a través del análisis de la producción científica y del análisis de contenido. Se han empleado Scopus y WOS para la identificación de los documentos. En el estudio bibliométrico se han analizado 92 artículos, y 43 de ellos para el análisis del contenido, por estar disponibles en abierto. Los resultados muestran el cumplimiento de las leyes cienciométricas y es relevante que los estudios con objetivo educativo, en horario escolar y en etapa de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
0
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
(48 reference statements)
2
0
0
2
Order By: Relevance
“…Secondly, based on Lotka's law, which focuses on the relationship between the number of documents and the number of authors writing on a topic, no major producers were identified in this study, as in previous investigations [59]. Thirdly, the distribution of publications in this study is observed in concentric zones of decreasing productivity, following Bradford's law and in line with previous work, such as that of [27]. Other results obtained in this study are in line with previous work using this approach, such as the preponderance of publications belonging to the USA [60], the weight of the journal Sustainability [61], the predominance of works corresponding to the field of health sciences [62,63], or the high degree of collaboration between authors [64].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Secondly, based on Lotka's law, which focuses on the relationship between the number of documents and the number of authors writing on a topic, no major producers were identified in this study, as in previous investigations [59]. Thirdly, the distribution of publications in this study is observed in concentric zones of decreasing productivity, following Bradford's law and in line with previous work, such as that of [27]. Other results obtained in this study are in line with previous work using this approach, such as the preponderance of publications belonging to the USA [60], the weight of the journal Sustainability [61], the predominance of works corresponding to the field of health sciences [62,63], or the high degree of collaboration between authors [64].…”
Section: Discussionsupporting
confidence: 85%
“…Thus, studies such as [23] or [24] highlight the benefits that these methods can bring to learning, concluding that they can improve student performance and competence development, and provide critical, meaningful, ubiquitous, transformative, and motivating experiences. This provides further evidence of their positive impact on educational processes, in line with previous studies such as [25], which supported mobile technology; [26], which analysed video tutorials as a teaching tool; and [27], which showed the impact of video games in physical education. These studies also confirmed that technology promotes the development of physical and psychological skills, enhances creativity and personal involvement, and facilitates an individualised pace of learning.…”
Section: The Impact Of the Pandemic On The Learning And Teaching Of P...supporting
confidence: 87%
“…Os jogos de realidade virtual são tecnologias recentes e, muito embora, sejam diferentes dos recursos eletrônicos tradicionais, utilizam como ferramenta os movimentos corporais (Santos et al, 2013;Marín et al, 2022).…”
Section: Introductionunclassified
“…Os Exergames (EXG), conhecidos como videogames ativos, Exergaming ou, ainda, Active Gaming, combinam EF com videogame, possibilitando o lúdico e a fascinação advindos da realidade virtual para serem utilizados na prática do EF, estimulando, assim, movimentações corporais semelhantes às atividades físicas convencionais (Vaghetti et al, 2013;Montilla et al, 2021;Marín et al, 2022).…”
Section: Introductionunclassified